Building bridges through art: how art education shapes Chinese views on Americans - Yuqi Su; Tingming Gao; Meng Tong; Yi Zhou (Intercultural Education, 2025)
Using data from the China Family Panel Studies (CFPS), this study examines the impact of art education on Chinese citizens’ trust in Americans. We find that participation in art tutorials correlates with increased trust towards Americans, with the level of trust rising with time spent in art education. Further analysis indicates that this effect is more pronounced in males and individuals whose parents already hold positive views of Americans. These results highlight the role of art education in fostering intercultural understanding. The study contributes to the literature on trust formation and the effects of art education, underscoring the significance of cultural engagement in promoting cross-cultural trust in global relations.